2016
DOI: 10.1007/s00709-016-0970-2
|View full text |Cite
|
Sign up to set email alerts
|

The right motifs for plant cell adhesion: what makes an adhesive site?

Abstract: Cells of multicellular organisms are surrounded by and attached to a matrix of fibrous polysaccharides and proteins known as the extracellular matrix. This fibrous network not only serves as a structural support to cells and tissues but also plays an integral part in the process as important as proliferation, differentiation, or defense. While at first sight, the extracellular matrices of plant and animals do not have much in common, a closer look reveals remarkable similarities. In particular, the proteins in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 190 publications
1
6
0
Order By: Relevance
“…Amphiphysin, actinin, and spectrin have no clear orthologs in plants; conversely, AFL1 has no clear metazoan ortholog. Similarly, others have predicted that the C-terminal region of At14a has some similarity to human Myosin XVIIIB, while the At14a N-terminal domain is weakly related to human dynein H chain 7 and laminin (Langhans et al, 2017). In addition to our previous work, one other study suggested that At14a affected both microtubule and actin filament organization in protoplasts (Lü et al, 2012).…”
supporting
confidence: 76%
See 1 more Smart Citation
“…Amphiphysin, actinin, and spectrin have no clear orthologs in plants; conversely, AFL1 has no clear metazoan ortholog. Similarly, others have predicted that the C-terminal region of At14a has some similarity to human Myosin XVIIIB, while the At14a N-terminal domain is weakly related to human dynein H chain 7 and laminin (Langhans et al, 2017). In addition to our previous work, one other study suggested that At14a affected both microtubule and actin filament organization in protoplasts (Lü et al, 2012).…”
supporting
confidence: 76%
“…However, the integrin similarity of At14a and AFL1 is limited to a small domain (now annotated as "Domain of Unknown Function 677"). Although some studies have suggested At14a (and AFL1) to be membrane-spanning proteins similar to mammalian integrins (Lü et al, 2012;Sardesai et al, 2013;Langhans et al, 2017), we found that AFL1 is a peripheral membrane protein associated with the plasma membrane and endoplasmic reticulum (ER; Kumar et al, 2015). AFL1 interacted with AP2-2a, an adaptor protein involved in cargo selection and clathrin-coated vesicle formation (Kumar et al, 2015).…”
mentioning
confidence: 49%
“…The integrity of cell walls and their adhesion to neighboring walls are essential for the support and protection of the plant body (Bouton et al, 2002;Verger et al, 2016;Langhans et al, 2017). However, growth and development requires that cell walls also can be fined-tuned to allow extension or detachment in some specialized cases (Roberts et al, 2002;Lewis et al, 2006;Ogawa et al, 2009;Swain et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Plant RGD-binding proteins are not only important for interactions between the cell wall and plasma membrane [ 103 , 104 ], they also play an important role in triggering ABA biosynthesis in response to osmotic stress, as artificial RGD-containing peptides have been found to block this process through competitive binding [ 105 , 106 ]. Although plants lack clear orthologs to mammalian RGD-binding integrins [ 107 ], a number of plant proteins that are capable of binding to RGD tripeptides have been identified, including integrin-like proteins [ 108 , 109 , 110 ], and some members of the large receptor-like kinase (RLK) family [ 111 ]. Some other, non-RGD binding members of the RLK family have also been linked to a role in sensing cell wall integrity, including wall associated kinases (WAKs) that bind pectins in the cell wall [ 112 ], and Catharanthus roseus RLK1-like proteins (CrRLK1Ls) and lectin receptor kinases (LecRKs), which have extracellular domains thought to bind carbohydrates from the intact cell wall or derived from degraded cell wall components [ 113 , 114 , 115 ].…”
Section: Possible Candidates For the Angiosperm Pathway For Rapid mentioning
confidence: 99%